GPR17 expressing NG2‐Glia: Oligodendrocyte progenitors serving as a reserve pool after injury. Issue 2 (14th October 2015) - Viganò, Francesca; Schneider, Sarah; Cimino, Mauro; Bonfanti, Elisabetta; Gelosa, Paolo; Sironi, Luigi; Abbracchio, Maria P.; Dimou, Leda
Abstract : In the adult brain NG2‐glia continuously generate mature, myelinating oligodendrocytes. To which extent the differentiation process is common to all NG2‐glia and whether distinct pools are recruited for repair under physiological and pathological conditions still needs clarification. Here, we aimed at investigating the differentiation potential of adult NG2‐glia that specifically express the G‐protein coupled receptor 17 (GPR17), a membrane receptor that regulates the differentiation of these cells at postnatal stages. To this aim, we generated the first BAC transgenic GPR17‐iCreER T2 mouse line for fate mapping studies. In these mice, under physiological conditions, GPR17 + cells —in contrast to GPR17 ‐ NG2‐glia— did not differentiate within 3 months, a peculiarity that was overcome after cerebral damage induced by acute injury or ischemia. After these insults, GPR17 + NG2‐glia rapidly reacted to the damage and underwent maturation, suggesting that they represent a 'reserve pool' of adult progenitors maintained for repair purposes. GLIA 2016;64:287–299 Main Points: GPR17 + NG2‐glia show a slow maturation capacity under physiological conditions. GPR17 + NG2‐glia react to injury like ischemia and acute lesion with differentiation. GPR17 + NG2‐glia represent a reservoir of progenitors responsible for brain repair.